2021
DOI: 10.3390/ani11113274
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance, Carcass Characteristics and Meat Quality of Organically Reared Broiler Chickens Depending on Sex

Abstract: Given the growing interest of consumers in naturally produced meat, we decided to examine the muscles of Ross 308 broiler chickens kept in an ecological system, with the division into two research groups depending on sex. All the analyses were carried out using the appropriate methods recommended by the AOAC and in accordance with the Polish standards (PN), which are described in detail in the relevant section of the publication. The aim of the experiment was to investigate the effect of sex on the growth perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 37 publications
1
8
1
Order By: Relevance
“…In fact, a negative correlation between breast muscle weight and glycogen stored in the muscle, i.e., a positive correlation of breast weight with the final pH, has been reported (Le Bihan-Duval et al, 2008). While we measured a higher shear force for cutting meat of male chickens, other authors found a lower value than female chickens which was attributed to the smaller fiber diameter in males (Cygan-Szczegielniak and Bogucka, 2021).…”
Section: Discussionmentioning
confidence: 43%
“…In fact, a negative correlation between breast muscle weight and glycogen stored in the muscle, i.e., a positive correlation of breast weight with the final pH, has been reported (Le Bihan-Duval et al, 2008). While we measured a higher shear force for cutting meat of male chickens, other authors found a lower value than female chickens which was attributed to the smaller fiber diameter in males (Cygan-Szczegielniak and Bogucka, 2021).…”
Section: Discussionmentioning
confidence: 43%
“…In our study, the higher final body weight of SP-treated chicks was not accompanied by a higher carcass percentage of the chickens. In general, the disparity results about the carcass percentage have been attributed to variances in chicken types (modern broiler versus native or crossbred chickens), age, sex, physical activity and environmental condition of chickens (Li et al 2017;Cygan-Szczegielniak and Bogucka 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The chemical composition of chicken meat is closely related to breeding, which means that genetics is the main influencing factor [ 1 , 17 , 18 ]. In this study, we found large moisture difference between breast muscle and thigh muscle, but not genders.…”
Section: Discussionmentioning
confidence: 99%